A comparative evaluation of the phenol and lycopene content of tomato by-products subjected to different drying methods. (1st April 2023) - Souza da Costa, Bianca; García, Marta Oliván; Muro, Germán Soldevilla; Motilva, Maria-Jose
Abstract: This study is focused on exploring tomato by-products to provide ingredients rich in bioactive compounds with higher functional value through applying innovative techniques (microwave and spiral flash dryer) and conventional techniques (freeze-drying and hot air-drying) to the dehydration of industrial tomato pomace. The effect of the drying method on the bioactive composition of the tomato by-products (phenols, lycopene and soluble dietary fiber) was analyzed. The phenolic composition was determined using a targeted chromatographic approach based on UHPLC-QqQ-MS/MS. Large amounts of naringenin (194.7–949.4 mg/kg) were detected, together with quercetin, caffeic acid, coumaric acid and 4-hydroxybenzoic acid. Microwave dehydration improved the retention of flavanone-like compounds, especially naringenin, and lycopene, while tomato products dehydrated with Spiral Flash dryer showed higher concentrations of flavonols and phenolic acids. The results showed that the industrial application of drying processes using Spiral Flash, and especially with microwaves, could be promising for producing high added-value ingredients from tomato by-products. Highlights: Tomato by-products source of naringenin with interesting nutraceutical properties. Microwave drying showed best results in naringenin retention in tomato by-products. Dehydration produces reduction in phenolic acid content in tomato by-products. Spiral Flash air drying industrial scale dehydration of tomato by-products.